Scalable image compression algorithms with small and fixed-size memory - Al-Janabi, Ali Kadhim; Harbi, Yahya J.; Hassan, Mohammed Falih (Signal, image and video processing, 2023)
The SPIHT image compression algorithm is characterized by low computational complexity, good performance, and the production of a quality scalable bitstream that can be decoded at several bit-rates with image quality enhancement as more bits are received. However, it suffers from the enormous computer memory consumption due to utilizing linked lists of size of about 2–3 times the image size. In addition, it does not exploit the multi-resolution feature of the wavelet transform to produce a resolution scalable bitstream by which the image can be decoded at numerous resolutions (sizes). The Single List SPIHT (SLS) algorithm resolved the high memory problem of SPIHT by using only one list of fixed size equals to just 1/4 the image size, and state marker bits with an average of 2.25 bits/pixel. This paper introduces two new algorithms that are based on SLS. Like SLS, the first algorithm also produces a quality scalable bitstream. However, it has lower time complexity and better performance than SLS. The second algorithm, which is the major contribution of the work, upgrades the first algorithm to produce a bitstream that is both quality and resolution scalable. As such, the algorithm is very suitable for the modern heterogeneous nature of the internet users to satisfy their different capabilities and desires in terms of image quality and resolution.